Back together: Over 1000 single-copy nuclear loci and reproductive features support the holoendoparasitic Apodanthaceae and Rafflesiaceae as sister lineages in the order Malpighiales (2024)
ABSTRACT: The systematics of the holoendoparasitic flowering plant families Apodanthaceae and Rafflesiaceae has been discussed for over two centuries. The morphological reduction of roots, shoots and leaves in all members of both families, resulting in a cryptic mycelium-like vegetative body, has been interpreted either as a key common feature, or as a result of convergent evolution due to full dependence upon their hosts. Historically, the two families have been placed together due to similar morphological features, but recent analyses based on few mitochondrial and ribosomal gene markers placed them in the distantly related orders Cucurbitales and Mal- pighiales. Here we reevaluate the affinities of the Apodanthaceae and the Rafflesiaceae using a phylogenomic approach. We present (1) a historical account on their affinities over the last 200 years; (2) phylogenetic analyses reinstating their sister group relationship as part of the order Malpighiales, based on over 1000 single-copy nuclear protein-coding loci; and (3) a comprehensive list of putative morphoanatomical and developmental synapomorphies in light of the phylogenomic results, with emphasis on shared reproductive traits regardless of dramatic differences in floral size.